Studi Analisa Potensi Sumber Air sebagai Pembangkit Listrik Tenaga Mikrohidro (PLTMH) di Karungan Kelurahan Mamburungan Timur Kota Tarakan - Hadi Santoso; Eris Santoso; Ruslim Ruslim (Jurnal Inovasi Sains dan Teknologi (INSTEK), 2021)
The supply of electrical energy in Tarakan City, North Kalimantan, still relies on diesel power which uses a limited number of petroleum energy sources. There is a need for research related to renewable energy sources that have the potential to become alternative energy for the people of Tarakan City. Water is an energy source that has great potential to generate electricity. The energy source that should be taken into account is micro-hydro which can be used as a Micro-hydro Power Plant (PLTMH). A survey of micro-hydro sources in Tarakan City, precisely in the Karungan area, East Mamburungan Village, has been carried out with the direct measurement method of water discharge and the relationship with the power generated. The result shows the water source has a discharge 0.00034 m3/ s, the water velocity of 0.035 m/s and generates power only up to 1.1 watts. Based on the power obtained, the water source in this place cannot be used as a source of micro-hydro energy, but has the potential as a source of pico-hydro energy.